Impact of COVID-19 vaccination on the risk of long COVID: An umbrella review of meta-analyses - Madenbayeva, Akzhan M.; Bazargaliyev , Yerlan Sh.; Kurmangaliyeva , Saulesh S.; Kudabayeva, Khatimya Kh.; Abilov, Talgar S. (Acta Biomedica Atenei Parmensis, 2026)
Background: Long COVID (post-acute COVID-19 syndrome) imposes a substantial burden on function, quality of life, and health services. Emerging evidence suggests COVID-19 vaccination may mitigate long-COVID risk, but estimates vary across syntheses and populations.Objectives: To evaluate the impact of COVID-19 vaccination on the risk of long COVID by consolidating evidence from systematic reviews/meta-analyses, assessing methodological quality, and quantifying primary-study overlap.Methods: We conducted an umbrella review of systematic reviews/meta-analyses indexed in PubMed, Scopus, and Web of Science (Dec 1, 2019–Sep 1, 2025; English). Eligibility followed PICOS; only SRs/MAs were included. Two reviewers screened, extracted data, and appraised quality with AMSTAR-2. Overlap of primary studies was quantified using the corrected covered area (CCA). Visual syntheses (AMSTAR-2 bubble plot; overlap matrix) were generated in RStudio (v4.3.1, ggplot2). Protocol registered on OSF.Results: Five meta-analyses met inclusion criteria. Across adult populations, vaccination was consistently associated with reduced long-COVID risk, with pooled vaccine effectiveness (VE) commonly ~29–41% for primary series. Timing and dose mattered: protection was stronger when vaccinated before infection, and booster doses yielded the largest effects (VE ~70%). Pediatric evidence was inconclusive, with pooled estimates not reaching statistical significance. AMSTAR-2 ratings were High (2 reviews), Moderate (2), and Low (1, pediatric). CCA indicated moderate overlap across reviews, suggesting that portions of the apparent consistency derive from shared primary cohorts.Conclusions: COVID-19 vaccination reduces the incidence of long COVID in adults, particularly when a complete primary series and booster doses are received prior to infection. Evidence in children/adolescents remains limited and non-definitive. Policymakers should prioritize completion of primary series and boosters as part of long-COVID prevention, while future research should standardize outcomes, extend follow-up, compare platforms/boosting schedules, and strengthen pediatric data.